Selective Neck Occlusion of a Large Complex Aneurysm of the Middle Cerebral Artery Trifurcation with the UltraSoft Coil - Benndorf, Goetz; Kroppenstedt, Stefan; Campi, Adriana; Unterberg, Andreas (American Journal of Neuroradiology, 2002)
Summary: We present a case of an unruptured, large, complex, middle cerebral artery trifurcation aneurysm that was successfully treated by selective occlusion of the neck with a single, newly available UltraSoft coil. The satisfactory initial anatomic result was stable, as demonstrated on a 3-month follow-up arteriogram that indicated complete anatomic cure. The novel UltraSoft coil offers additional possibilities in the endovascular management of difficult-to-treat vascular lesions.